1998
DOI: 10.1046/j.1523-1747.1998.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Type Matrix Metalloproteinases in Human Dermal Microvascular Endothelial Cells: Expression and Morphogenetic Correlation

Abstract: Membrane-type matrix metalloproteinases (MT-MMP) activate the zymogen form of MMP-2/Gelatinase A on cell surfaces and are expressed in invasive tumors. We sought to identify and characterize MT-MMP in a non-malignant cell type that undergoes a physiologic and reversible invasive phenotype during angiogenesis. Human dermal microvascular endothelial cells (HDMEC) were isolated from neonatal tissue and purified by anti-CD31 (PECAM) affinity beads. MT-MMP-1 and -3 transcripts were amplified by reverse transcriptas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…We also report a preferential involvement of MT1-MMP in CCL2-and CXCL8-versus CXCL12-induced angiogenesis in human ECs. Our data show that CCL2 and CXCL8, but not CXCL12, increased MT1-MMP surface expression in ECs similar to other angiogenic factors and inflammatory cytokines (31,32), in this case by partially inhibiting MT1-MMP internalization. In addition, CCL2 and CXCL8 increased MT1-MMP clustering at endothelial membrane protrusions, and this correlated with an increase in MT1-MMP activity.…”
Section: Discussionmentioning
confidence: 49%
“…We also report a preferential involvement of MT1-MMP in CCL2-and CXCL8-versus CXCL12-induced angiogenesis in human ECs. Our data show that CCL2 and CXCL8, but not CXCL12, increased MT1-MMP surface expression in ECs similar to other angiogenic factors and inflammatory cytokines (31,32), in this case by partially inhibiting MT1-MMP internalization. In addition, CCL2 and CXCL8 increased MT1-MMP clustering at endothelial membrane protrusions, and this correlated with an increase in MT1-MMP activity.…”
Section: Discussionmentioning
confidence: 49%
“…Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR)-A total of 3 g of isolated RNA was subjected to first strand cDNA synthesis with Moloney-murine leukemia virus reverse transcriptase, RNase inhibitor (Roche Molecular Biochemicals), and oligo(dT) [12][13][14][15][16][17][18] primer (Life Technologies, Inc.) for 1 h at 37°C according to the manufacturer's instructions. One-tenth of the cDNA generated from the reverse transcriptase reaction was used for PCR amplification in the presence of Taq DNA polymerase (Roche Molecular Biochemicals) and oligonucleotide primers, 5Ј-CAG ATC TTC GGG GAC TAT TAC CAC-3Ј (sense) and 5Ј-CCT GTT GTC ATT CAT CTG TGT GTA CC-3Ј (antisense).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that MT1-MMP is an endogenous activator of pro-MMP-2 (9). On the other hand, the increased expression of MT1-MMP has been correlated with physiological and pathological events such as embryogenesis (10), wound healing (11), angiogenesis (12), rheumatoid arthritis (13), osteoarthritis (14). and tumor invasion (15)(16)(17).…”
Section: Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…39 The evidence so far The smoking gun Already a substantial body of circumstantial evidence links the MMPs to angiogenesis. In vitro, endothelial cells (ECs) express a range of MMPs as well as TIMP-1, -2 and -3 [40][41][42] and it has been demonstrated that endothelial MMP expression and activity can be modulated by angiogenic factors. [43][44][45][46] Upregulated MMP expression has also been observed in blood vessels in vivo in several physiologic and pathologic conditions, indicating that MMPs are involved in the activity of the endothelium during these processes.…”
Section: Endogenous Inhibitors Of Metalloproteinasesmentioning
confidence: 99%